2021
DOI: 10.1101/2021.04.15.439938
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Vaccinia virus subverts xenophagy through phosphorylation and nuclear targeting of p62

Abstract: Autophagy is an essential degradation program required to maintain cell homeostasis. Amongst its many functions is the engulfment and destruction of cytosolic pathogens, termed Xenophagy. Not surprisingly, many pathogens have adapted various strategies to circumvent or co-opt autophagic degradation during infection. For poxviruses, it is known that infection activates autophagy, which however is not required for successful replication. Despite the fact that these complex viruses replicate exclusively in the cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 75 publications
(84 reference statements)
0
3
0
Order By: Relevance
“…Moreover, vaccinia-and papillomaviruses oppose the p62 requirement for infection, as p62 restricts vaccinia while supporting HPV16 infection. In the context of In this scenario, HPV16-induced signal transduction might contribute to p62 phosphorylation and its translocation into the nucleus as described during vaccinia virus infection [61]. Here, p62 is phosphorylated by a vaccinia virus kinase that is not present in papillomaviruses.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, vaccinia-and papillomaviruses oppose the p62 requirement for infection, as p62 restricts vaccinia while supporting HPV16 infection. In the context of In this scenario, HPV16-induced signal transduction might contribute to p62 phosphorylation and its translocation into the nucleus as described during vaccinia virus infection [61]. Here, p62 is phosphorylated by a vaccinia virus kinase that is not present in papillomaviruses.…”
Section: Discussionmentioning
confidence: 97%
“…In this scenario, HPV16-induced signal transduction might contribute to p62 phosphorylation and its translocation into the nucleus as described during vaccinia virus infection [ 61 ]. Here, p62 is phosphorylated by a vaccinia virus kinase that is not present in papillomaviruses.…”
Section: Discussionmentioning
confidence: 99%
“…A previous report indicated that the deletion of ATG5 and Beclin 1 from mouse embryonic fibroblasts (MEF) did not impact VACV’s replication 31 . A previous report indicated that Vaccinia virus subverts xenophagy through phosphorylation and nuclear targeting of p62 and nuclear translocation of p62 was dependent upon p62 NLS2 and correlated with VACV kinase B1 and F10 mediated phosphorylation of p62 T269/S272 37 . In this study, we demonstrated that pharmaceutical inhibition or the suppression of ATG16L1 significantly impaired the replication of VACV-WR, MVA and LSDV.…”
Section: Discussionmentioning
confidence: 90%